Perancangan dan Evaluasi Antarmuka Platform Pembelajaran Pengurangan Sampah Makanan pada Studi Kasus Mama4Planet - Lina Fitra; Harry Budi Santoso (AI Society & STMIK Indonesia, 2025)
This research is driven by the need to promote behavioral change through education on reducing food waste, as exemplified by the initiatives of Mama4Planet. Therefore, there is a need to develop a digital learning media that meets the needs of stakeholders and users through interface design. This research uses a user-centered design approach. Requirement discovery was carried out through stakeholder and 15 user interviews so that the outputs were three user personas, user journey maps, and value proposition canvases. A total of 8 user flows and 19 wireframes were also the outputs of this phase. Furthermore, prototyping was carried out by providing interactions between pages and other components that refer to the user flow. The evaluation stage was done through two iterations of usability testing with results showing an increase in completion rate, time-based efficiency, and SUS score from 63.8 or grade C- to 79.0 or A-.